FEASIBILITY STUDY FOR SOLAR POWER PLANT IMPLEMENTATION IN UTP - Mohd Zain, Muhammad Afiq (Universiti Teknologi PETRONAS, 2018)
There are many types of power plant that are currently being operate in Malaysia to generate electricity to supply across Malaysia. For university Teknologi Petronas or UTP, it generates its own electricity by having it own power plant. The type of power plant in UTP are gas turbine or GT located at gas district cooling or GDC. This power plant run on natural gas supply through underground piping directly from Petronas. This power plant can roughly generate up to 8 MW per day to supply electrical to UTP buildings. This power plant is operated by third party company which is Mahkostia S/B.